2022
DOI: 10.1364/optcon.451627
|View full text |Cite
|
Sign up to set email alerts
|

Coherent beam amplification with dynamic holograms in glass-forming molecular azobenzene-based materials

Abstract: Self-diffraction of two coherent light waves that record a holographic grating in thin films of azobenzene-containing molecular glass-forming materials is used for intensity enhancement of a weak beam in expense of the strong beam intensity. The intensity of a weak probe beam is doubled at interaction length of only 8 µm thus pointing to a very high specific coupling constant. The characteristic time of the intensity redistribution is relatively long, on the order of 200 s. Consequently, the underlying process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…These materials have found numerous applications in optoelectronics including holographic information recording and holographic light amplification [4,5]. In the recent years, azobenzene molecular glassy films have attracted attention in this respect [6][7][8]. It was concluded that grating recording and readout by orthogonal circularly polarized (L-left rotation of the electric field vector of light or R-its right rotation) light beams is the most efficient.…”
Section: Introductionmentioning
confidence: 99%
“…These materials have found numerous applications in optoelectronics including holographic information recording and holographic light amplification [4,5]. In the recent years, azobenzene molecular glassy films have attracted attention in this respect [6][7][8]. It was concluded that grating recording and readout by orthogonal circularly polarized (L-left rotation of the electric field vector of light or R-its right rotation) light beams is the most efficient.…”
Section: Introductionmentioning
confidence: 99%